HnRNP A1 dysfunction in oligodendrocytes contributes to the pathogenesis of multiple sclerosis. Issue 3 (16th November 2022) - Jahanbazi Jahan‐Abad, Ali; Salapa, Hannah E.; Libner, Cole D.; Thibault, Patricia A.; Levin, Michael C.
Abstract: Oligodendrocyte (OL) damage and death are prominent features of multiple sclerosis (MS) pathology, yet mechanisms contributing to OL loss are incompletely understood. Dysfunctional RNA binding proteins (RBPs), hallmarked by nucleocytoplasmic mislocalization and altered expression, have been shown to result in cell loss in neurologic diseases, including in MS. Since we previously observed that the RBP heterogeneous nuclear ribonucleoprotein A1 (hnRNP A1) was dysfunctional in neurons in MS, we hypothesized that it might also contribute to OL pathology in MS and relevant models. We discovered that hnRNP A1 dysfunction is characteristic of OLs in MS brains. These findings were recapitulated in the experimental autoimmune encephalomyelitis (EAE) mouse model of MS, where hnRNP A1 dysfunction was characteristic of OLs, including oligodendrocyte precursor cells and mature OLs in which hnRNP A1 dysfunction correlated with demyelination. We also found that hnRNP A1 dysfunction was induced by IFNγ, indicating that inflammation influences hnRNP A1 function. To fully understand the effects of hnRNP A1 dysfunction on OLs, we performed siRNA knockdown of hnRNP A1, followed by RNA sequencing. RNA sequencing detected over 4000 differentially expressed transcripts revealing alterations to RNA metabolism, cell morphology, and programmed cell death pathways. We confirmed that hnRNP A1 knockdown was detrimental to OLs and induced apoptosis and necroptosis. Together, these data demonstrate a critical role for hnRNP A1 in proper OL functioning and survival and suggest a potential mechanism of OL damage and death in MS that involves hnRNP A1 dysfunction. Main Points: Dysfunction of the RNA binding protein hnRNP A1 is characteristic of OLs from MS and relevant models. hnRNP A1 is critical for OL health. Knockdown of hnRNP A1 in OLs negatively impacts morphology, increases cytotoxicity, and activates programmed cell death pathways.